Formation of SiO2@SnO2 core–shell nanofibers and their gas sensing properties. Issue 16 (2nd February 2016) - Liu, Yunshi; Yang, Ping; Li, Jia; Matras-Postolek, Katarzyna; Yue, Yunlong; Huang, Baibiao
Abstract : SiO2 @SnO2 core–shell nanofibers were prepared by a single-spinneret electrospinning route and subsequent calcination process. Both the ratio of Sn and Si and the special core–shell structure played significant roles in gas sensing performance. Abstract : SiO2 @SnO2 core–shell nanofibers (NFs) were successfully prepared by single-spinneret electrospinning and subsequent calcination process. The precursor solutions were prepared from poly(vinylpyrrolidone), SnO2 precursors, and tetraethylorthosilicate (TEOS) with prehydrolysis. The prehydrolysis of TEOS plays an important role for the formation of core–shell structure. After calcining, the resulting fiber sample had an amorphous SiO2 core and a shell consisted of SnO2 particles. The fibers with various morphologies were obtained through adjusting the molar ratio of Sn and Si and the possible formation mechanism of core–shell NFs was proposed. Both Kirkendall effect and grain growth played important roles for the formation of core–shell structure. Furthermore, SiO2 was used as support material to fix the SnO2 particles and avoid the collapse of the SnO2 structure. The amount of SnO2 precursors directly determined the compactness of the shell, resulting in the different gas sensing properties. The SiO2 @SnO2 core–shell NF network sensor responds to ethanol, ammonia, benzene, toluene, chloroform, and hexane gases, but it exhibited enhanced gas response to ethanol with a short response time. Those SnO2 particles formed on the exterior of the fibers provided lots of contact area with the target gas to reduce resistance. In addition, the connectivity between particles also had certain influence on the electrical conductivity of the sample. The results demonstrate that single-spinneret electrospinning can also be used to prepare core–shell fibers with various applications.